EFECTOS DE DISTINTOS TRATAMIENTOS EN VIVERO EN EL ARRAIGO Y PRIMER DESARROLLO EN CAMPO DE PLANTAS DE QUERCUS SUBER L. y QUERCUS ROTUNDIFOLIA LAM .. EFECTO DEL PROTECTOR. (II Congreso Forestal Español, 1997)
The rootting ability and the first developes of cork oak and olm oak seedlings cultivated on different substratums and containers, as well as different harding degrees are comparied. The individual protector's effect is also analyzed.